2022
DOI: 10.1038/s42949-022-00068-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pandemic outdoor recreation and green infrastructure in Nordic cities to enhance urban resilience

Abstract: Recent empirical research has confirmed the importance of green infrastructure and outdoor recreation to urban people’s well-being during the COVID-19 pandemic. However, only a few studies provide cross-city analyses. We analyse outdoor recreation behaviour across four Nordic cities ranging from metropolitan areas to a middle-sized city. We collected map-based survey data from residents (n = 469–4992) in spring 2020 and spatially analyse green infrastructure near mapped outdoor recreation sites and respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Additionally, a previous review in environmental research has also pointed out the benefits of accessing green space on improving wellbeing, by reducing exposure to environmental stressors, restoring capacities, and building capacities 19 . Recently, urban research also showed that green infrastructure across cities can interplay with respondents' residential locations, as well as their socio-demographic profiles and lockdown policies, to predict residents' outdoor recreation behaviour 44 . In fact, the unequal access to green spaces presents a troubling picture to policymakers, as individuals who live more than 800 m away from green spaces tended to travel less to green spaces…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a previous review in environmental research has also pointed out the benefits of accessing green space on improving wellbeing, by reducing exposure to environmental stressors, restoring capacities, and building capacities 19 . Recently, urban research also showed that green infrastructure across cities can interplay with respondents' residential locations, as well as their socio-demographic profiles and lockdown policies, to predict residents' outdoor recreation behaviour 44 . In fact, the unequal access to green spaces presents a troubling picture to policymakers, as individuals who live more than 800 m away from green spaces tended to travel less to green spaces…”
Section: Discussionmentioning
confidence: 99%
“…Within the City of Sheffield, the valuing of the cultural element of the city centre was notable, for which we propose an additional subcategory of ‘Arts & Culture’ value (which comprised 15 per cent of all ‘Communal’ value). It also became clear that 35 per cent of all personal connections to place were based on experiences during the COVID-19 pandemic and with a strong orientation toward the use of landscape for mental and physical health benefits (Fagerholm et al 2022). Therefore, we propose the introduction of the category ‘Green Space’ value to bridge the artificial division between natural and cultural heritage.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors focus on technologies and digitization (Sharifi & Salehi, 2022), others focus on increasing the share of green infrastructure, which could bring health benefits (Fagerholm et al, 2021). The importance of spatial planning for ensuring human well-being in exceptional situations has been demonstrated (Fagerholm et al, 2022). Experts have scientifically proven that naturebased solutions integrated into urban policies and strategies improve the resilience and equity of cities, reduce the impact of climate change and contribute to the development of urban sustainability (Bayulken et al, 2020).…”
Section: Dimensions Analysis Based On Publications In the Dimensions ...mentioning
confidence: 99%